Penguatan Manajemen Produksi dengan Penerapan Konsep 3R (Recycle, Reduce and Reuse) pada Agroindustri Makanan Ringan di Kelurahan Lubuk Minturun, Kota Padang - Rini Hakimi; Rika Hariance; Syahyana Raesi; Rusyja Rustam; Rina Sari; Vonny Indah Mutiara; Zednita Azriani; Widya Fitriana; Dian Hafizah; Ifdal Ifdal; Cipta Budiman; Yusmarni Yusmarni; Afrianingsih Afrianingsih; Daddy Budiman (Warta Pengabdian Andalas, 2023)
Snack food agro-industry is a potential agribusiness to be developed. Agro-industrial activities produce fresh waste that has yet to be utilized. This waste is in the form of organic solid and liquid waste. Waste left or disposed of will result in pollution. The solution to solve these problems is that waste can be recycled, reduced, and reused, named the 3R concept. This community activity involved advanced service methods, including education and demonstrations to apply the 3R concept for waste—further, the activity team also handovers decomposers and some useful equipment’s for making compost. About ten snack agro-industries attended this service activity. The extension service has provided an understanding to the snack agro-industry regarding implementing 3R and alternatives to reduce the amount of their fresh waste. Demonstrations were related to recycling solid waste into compost and assembling filtering equipment to purify liquid waste. This agro-industry counselling needs to be sustained to consistently apply the 3R concept in the production activities carried out.